The Community Structure of R&D Cooperation in Europe. Evidence from a social networks perspective - Michael J. Barber; Manfred M. Fischer; Thomas Scherngell (European Regional Science Association (ERSA), 2010)
The focus of this paper is on pre-competitive R&D cooperation across Europe, as captured by R&D joint ventures funded by the European Commission in the time period 2002-2006, within the 5th Framework Program. The cooperations in this Framework Program give rise to a collaborative network, with network nodes representing actors (i.e. organizations including firms, universities, research organizations and public agencies) and network edges representing R&D projects. With this construction, participating actors are linked only through joint projects. We formally describe and analyze the network from a social networks perspective that shifts attention to the detection and analysis of the community structure within the network. Distinct communities within networks may be loosely defined as groups of actors such that there is a higher density of relations within groups than between them. In this study, we attempt to detect communities of actors solely on the basis of the relational structure within the network, and to characterize and differentiate the identified network communities by means of information-theoretic methods, community-specific profiles and the location of their major actors. We expect the results to enrich our picture of the European research area by providing new insights into the global and local structures of R&D cooperation across Europe.
Keywords: 330